Alternative biosorbents from agro-industrial waste: a review for application in the removal of organic pollutants - Pedebos, Maria Eduarda; Santos da Rosa, Gabriel; Druzian, Daniel Moro; da Silva, Maurício Dalla Costa Rodrigues; da Silva, William Leonardo (Disciplinarum Scientia | Naturais e Tecnológicas, 2024)
Environmental conservation issues are widespread today because of the scarcity of renewable resources. Faced with this, pollution of water resources becomes a cause for concern, as its treatment is not feasible. As in Brazil there is a significant production of agro-industrial products, its residues also become worrisome if not discarded correctly. As a result of this, the alternative biosorbents that derive from the use of the agro(industrial) residues and that aid in the process of treatment of effluents arise. To solve the problem of water pollution, a viable alternative is the adsorption with the use of alternative biosorbents for removal of undesirable components. In this context, the present work presents a study on the application in the removal of organic pollutants from effluents from alternative biosorbents from agro(industrial) waste.